THE TAG AS A SURVEILLANCE CELL. A critical view of metadata and facial recognition systems through artistic practices - López-Cleries, Gloria (ANIAV, 2017)
[EN] Nowadays, the expansion of social networks has made possible the emergence of a new, decentralized and diffused surveillance model. Web 2.0 and smartphone devices allow the circulation of private information available to users and public-private companies that are part of the new network economy. The daily use of applications with gps locator allows the storage of all kinds of activities and to carrying out the reconstruction of all our actions, desires and affections. In a context of hyper-exposure, of the hyper-connected 24/7 society, it is considered to be as a new model of more diffused surveillance, but maintaining the same effect of the Panopticon. This has an impact on user psychology creating a disciplinary power in the face of uncertainty of being under constant surveillance. The concept of Panopticon's isolation and surveillance cell is reflected today, not only in each personalized account in social networks, but in all the information that is recorded in the Google history associated with a personal email account, Paypal accounts and countless apps that register heart rate, fingerprints, sleep curves and blood sugar. These applications allow the total registration of all physical, biological and affective actions and movements. From Foucault’s perspective, social media is more than a vehicle for the exchange of information, it is a vehicle for the formation of identity and its control.[ES] En la actualidad la expansión de las redes sociales ha hecho posible la aparición de un nuevo modelo de vigilancia más descentralizado y más difuso. La web 2.0 y los dispositivos smartphone permiten poner en tránsito información privada a disposición de los usuarios y de empresas público - privadas que forman parte de la nueva economía de red. La cotidianización de las aplicaciones con geolocalizadores permiten almacenar todo tipo de actividades y realizar la reconstrucción de todas nuestras acciones, deseos y afectos. En un contexto de hiper-exposición, de la sociedad hiper-conectada 24/7, se alza como un nuevo modelo de vigilancia más difuso, pero manteniendo el mismo efecto del Panóptico, que impacta sobre la psicología user creando un poder disciplinario ante la incertidumbre de estar en un foco de vigilancia.La celda de aislamiento y vigilancia del Panóptico se convierte hoy no solo en cada cuenta personalizada en las redes sociales sino en toda la información que registra el historial de Google asociado a una cuenta de mail personal, a cuentas de Paypal y a infinidad de apps que registran el ritmo cardíaco, las huellas digitales, las curvas de sueño y el azúcar en la sangre. Estas aplicaciones permiten el registro total de todas las acciones y movimientos físicos, biológicos y afectivos. Desde una perspectiva foucaultiana, los medios de comunicación social (social media) son más que un vehículo para el intercambio de información, son un vehículo para la formación de la identidad y su control.López-Cleries, G.; Porras Soriano, Á. (2018). EL TAG COMO CELDA DE VIGILANCIA. Una visión crítica de los metadatos y sistemas de reconocimiento facial a través de las prácticas artísticas. ANIAV - Revista de Investigación en Artes Visuales. (2):99-107. https://doi.org/10.4995/aniav.2018.9123SWORD991072Blas, Z. (2013). Contra-Internet aesthetics. En O. Kholeif (ed.). You Are Here. Art After the Internet (p. 90). Manchester: Cornerhouse Publications.Chomsky, N. (2006). Sobre democracia y educación. Escritos sobre las instituciones educativas y el lenguaje en las aulas; C.P. Otero (compilador). Barcelona: Ed. Paidós Ibérica S.A.Crary, J. (2015). 24/7: Capitalismo tardío y el fin del sue-o. Barcelona: Ed. Ariel.Foucault, M. (2000). Vigilar y Castigar. Nacimiento de la prisión. Argentina: Editorial Siglo XXI.Han, B-C. (2014). Psicopolitica: Neoliberalismo y nuevas técnicas de poder. Barcelona: Ed. Herder.Keen, A. (2016). Internet no es la respuesta. Barcelona: Ed. Catedral.Morozov, E. (2012). El desenga-o de Internet, Los mitos de la libertad en la red. Barcelona: Ed. Destino